A Cognitive Perspective on the Business Case for Corporate Sustainability. (4th March 2014) - Hockerts, Kai
Abstract This paper proposes that a cognitive perspective on corporate sustainability and competitiveness might allow new insights into the question of the business case. The paper explores how respondents from 12 firms make sense of their firm's investments in corporate sustainability activities by analyzing the mental models evoked. The interviews showed that a business case perspective emerged as the dominant logic. A subsequent analysis of the content of the knowledge schemas that were elicited surfaced four dimensions of corporate sustainability induced competitive advantages: risk reduction, efficiency gains, brand building and new market creation. An analysis of the structure of these knowledge schemas revealed that respondents from firms with lower perceived sustainability performance drew on less differentiated and less integrated cognitive frameworks (focusing on risk and efficiency). Respondents from firms with higher perceived performance drew on more complex mental models to represent the links between corporate sustainability and competitiveness. Copyright © 2014 John Wiley & Sons, Ltd and ERP Environment